DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN SUB SEKTOR BATUBARA DAN NON BATUBARA YANG LISTED DI BURSA EFEK INDONESIA - Yusuf Fatoni; Hadi Paramu; Elok Sri Utami (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2013)
The objective of this research is to analyze the influence of partial and simultaneous determinants of capital structure, including the cost of debt, business risk, size, growth, dividend policy, and profitability. This research also analyzes the influence of differences the capital structure determinants in two different sub sectors. Listed sub sector of coal mining and non coal mining companies at Indonesia Stock Exchange period 2008-2012 were examined. Based on the census method, 17 coal mining companies and 14 non coal mining companies were included in the research. This research applied multiple regression analysis and Chow test. The result showed that simultaneously, all six independent variables do not significantly affect the capital structure on the sub sector of coal mining but significantly affect it on the sub sector of non coal mining. Partially, the influence of six independent variables varied in sub sector of coal mining and non coal mining. The result of Chow test showed that all variables has a different influence on the capital structure between those two sub sectors. Key words: capital sructure, cost of debt, business risk, size, growth, dividend policy.